2006
DOI: 10.1111/j.1600-9657.2006.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of MTA and intracanal post reinforcement in a horizontally fractured tooth: a case report

Abstract: Root fracture is one of the consequences of dental traumatisms. The possibility of saving the fractured tooth depends on the level of the fracture and also on pulp vitality. This case report describes the use of MTA in association to an intracanal post to reinforce a maxillary central incisor with horizontal root fracture in its cervical third.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…59 More recently, the use of MTA has been recommended in some cases. 8,63 Early and accurate repositioning of the coronal fragment has been shown to reduce the likelihood of pulp necrosis. 64 Optimum repositioning should be verified radiographically.…”
Section: Root Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…59 More recently, the use of MTA has been recommended in some cases. 8,63 Early and accurate repositioning of the coronal fragment has been shown to reduce the likelihood of pulp necrosis. 64 Optimum repositioning should be verified radiographically.…”
Section: Root Fracturesmentioning
confidence: 99%
“…In general, if pulp necrosis occurs, it will be confined to the coronal fragment. Should pulp necrosis develop, temporary filling of the root canal with calcium hydroxide for four to six months to the level of the fracture followed by root filling with gutta-percha or MTA 8,63 to that level is the treatment of choice. Under no circumstances should the pulp be removed beyond the level of the fracture in the first instance as doing so will compromise the long-term success of treatment.…”
Section: Endodontic Treatment Of Root-fractured Teethmentioning
confidence: 99%
“…A few cases were reported to use titanium posts clinically in immature teeth. 7) Fiber posts have similar elastic modulus with dentin and can bond with resin cement through surface treatment and bonding procedure. In addition, fiber posts can transmit light to deeper part of the canal so they can improve degree of polymerization of resin cements.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…6) Recently, a clinical approach has been introduced to use titanium post and MTA for root reinforcement. 7) Ideal materials for root reinforcement should bond to root dentin and have a similar elastic modulus with root dentin. 8) MTA lacks of bonding to dentin and has low strength in tension.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Some studies reported that when MTA is used for orthograde root canal filling, its sealing ability is inferior 15) or superior 16) to that of gutta-percha. A few studies have shown that MTA is an effective root reinforcement material 17,18) . However, one of the drawbacks of MTA is the difficulty of its handling.…”
Section: Introductionmentioning
confidence: 99%